30.1k views
1 vote
Show how you got the answer.
3d-5-2d=-9

User Tommy
by
5.9k points

2 Answers

3 votes
3d - 5 - 2d = -9

The first step is to combine like terms.

3d - 2d = d

d - 5 = -9

Next, we add 5 to both sides to isolate d.

d - 5(+5) = -9(+5)
d = -9 + 5
d = -4

Lastly, it is good to check your work by plugging your answer into the original equation.

3d - 5 - 2d = -9
3(-4) - 5 - 2(-4) = -9

The first step is to multiply:

3(-4) = -12
-2(-4) = 8

We plug those in and solve:

-12 - 5 + 8 = -9
-12 - 5 = -17
-17 + 8 = -9
-9 = -9



The answer is d = -4
User Deon
by
5.6k points
6 votes
3d-5-2d=-9
Combine like terms
(3d-2d) -5=-9
d-5= -9
Add 5 to both sides
d= -4

Check:
Substitute d=-4 into equation
3d-5-2d=-9
3(-4)-5-2(-4)=-9
-12-5+8=-9
-17+8=-9
-9=-9

Hope this helps! :)
User Saim Mehmood
by
6.4k points